Analysis of artistic anthropology of the novel by A.P. Platonov's «Kotlovan» in literature lessons (Eurasian Journal of Philology Science and Education, 2020)
A.P. Platonov is a great reformer of Russian fiction. In the process of development of the Russian novel, dedicated two of his main genre varieties: anthropological and ontological affair. Anthropological novel emerged and developed in the Russian realist literature of the nineteenth century. Ontological novel is the new genre that emerged in the works of A. Platonov and A. Bely. The writer in his works from other positions than his great predecessors portrayed literary heroes. A.P. Platonov adheres to the principle of minimalism in his work. The minimalism of the creative method A.P. Platonov is expressed in the fact that his literary characters (unlike the heroes of classical realistic literature) are endowed with reduced external, psychological characteristics and properties. The Story of A.P. Platonov's «Kotlovan» differs from the works of Russian literary classics, which drew full-blooded heroes endowed with a variety of qualities and properties. In the story «Kotlovan» the system of ontological images has a high semantic status. It also distinguishes the poetics of this story from classical realistic literature. For A.P. Platonov's main thing is to show not a holistic image of a person, but his stay in being. Therefore, the writer succinctly drew his characters and endowed the images of space and time with high artistic status. This article presents a consistent description of methodological techniques and methods for analyzing artistic anthropology and the problems of the story «Kotlovan» at school. The heuristic approach will provide favorable conditions for the deep and lasting assimilation by students of the poetics, style and problems of this work by A.P. Platonov.